Factors affecting the readiness of digital transformation adopters: A case study in Vietnam - Vinh T. Nguyen; Hue T. Lai; Quynh V. Ha (Northern Negros State College of Science and Technology (NONESCOST), 2023)
In the age of industry 4.0, digital transformation is becoming an increasingly popular term. Prior studies concentrated on advantages and research agenda, but little attempts were made to comprehend and evaluate the postulated conceptual model. Thus, the aim of this research was to understand the latent variables that affected the readiness of digital transformation adopters as well as the importance level between those dimensions. The 12-question survey was designed using Google Form and sent to 97 students of the digital transformation training class. Exploratory factor analysis and multivariate regression were utilized to analyze the obtained survey data. The findings showed that there were 4 main factors affecting the readiness of digital transformation including awareness, facilitating conditions, knowledge and behavioral intention. The total variance extracted by these 4 factors explained 61% of the data variation of 12 observed variables. The results of multivariable regression analysis demonstrated that all extracted factors had an important influence on the readiness of students to transform digitally, in which "behavioral intention" played the most important role. The research results help policy makers and educators have a better overview, thereby making strategies and adjusting plans according to the priority level around the above 4 factors. It also serves as a basis for other in-depth studies, and as a reference for interested digital transformation readers.